Germany's Three-Pillar Banking System : Cross-Country Perspectives in Europe. (Occasional Papers; Occasional Paper ;, 2004)
German banks tend to be less profitable than their foreign counterparts. This paper estimates the likely effect of the phaseout of state guarantees for public sector banks, reviews the various ways in which public policy could contribute to their restructuring, and discusses the various arguments for and against public involvement in banking.